2018
DOI: 10.1007/s11095-018-2545-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tryptophan Oxidation in Complementarity-Determining Regions of Two Monoclonal Antibodies on Structure-Function Characterized by Hydrogen-Deuterium Exchange Mass Spectrometry and Surface Plasmon Resonance

Abstract: PurposeTryptophan’s (Trp) unique hydrophobic and structural properties make it an important antigen binding motif when positioned in complementarity-determining regions (CDRs) of monoclonal antibodies (mAbs). Oxidation of Trp residues within the CDR can deleteriously impact antigen binding, particularly if the CDR conformation is altered. The goal of this study was to evaluate the conformational and functional impact of Trp oxidation for two mAb subtypes, which is essential in determining the structure-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…17 It has also been reported that oxidation of a CDR tryptophan residue significantly reduces antigen binding affinity, and HDX-MS data have revealed that the modifications increase the flexibility of variable regions and disrupt local conformation. 18 Although a similar experiment with Asn deamidation revealed no measurable local conformational changes caused by the modification, this finding may have been compromised by the low deamidation levels (~30%) in the material used in the study. 19 A few studies have explored how Asn deamidation affects the three-dimensional structure of proteins.…”
Section: Introductionmentioning
confidence: 79%
“…17 It has also been reported that oxidation of a CDR tryptophan residue significantly reduces antigen binding affinity, and HDX-MS data have revealed that the modifications increase the flexibility of variable regions and disrupt local conformation. 18 Although a similar experiment with Asn deamidation revealed no measurable local conformational changes caused by the modification, this finding may have been compromised by the low deamidation levels (~30%) in the material used in the study. 19 A few studies have explored how Asn deamidation affects the three-dimensional structure of proteins.…”
Section: Introductionmentioning
confidence: 79%
“…As M55 is located in the CDR2, the oxidation of this residue may directly impact the target binding [38]. Oxidation of methionines as well as of trypthophanes in the CDRs can result in destabilisation of Fab, increased aggregation as well as decreased target binding [9,19,41]. Pisupati et al performed a comparability study between infliximab and the biosimilar Remsima [28].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of these biological reagents is known to be dependent on their route of manufacture and can differ even between batches of the same product from a single manufacturer. For instance, differences in the posttranslational modification of biological molecules can have profound effects on their activity both in vitro and in vivo; examples include sialylation [6], oxidation [7], sulfation [8], and disulfide bond reduction/oxidation [912]. As a result, the addition of biological reagents to cell culture based on mass or concentration (i.e., mg/ml) may lead to inconsistent or irreproducible effects on the cells, which would then be an unknown and uncontrolled experimental variable.…”
Section: Metrology In Biologymentioning
confidence: 99%